Artefact. - Buhles, Stefanie; Bürli, Peter; Deidesheimer, Bernd; Fehrenbach, Frank; Haldemann, Matthias; Hauser, Stephan E.; Janzen, Thomas; Lüthy, Michael; Mumenthaler, Alfredo; Müller, Harald F.; Paul, Frédéric; Schreier, Christoph; et al. (Basel : Wiese Verlag, 1988)
Bohlen, Jürg ; Bonato, Victor ; B.P. ; Hotzel, Hans-Dirk ; Landrock-Schumann, Hannelore ; Mathis, Muda ; Müller, Harald F. ; Mumenthaler, Ursula ; Porret, Gilles ; Reichlin, Beat ; Schaffner, Heinz ; Spahni, Philippe ; Walser, Käthe ; Wolfensberger, Andrea
Artefact, F. Aeschbach AG, Aarau, Oktober 1988
Duits
boek